Animism as a Key to Remodelling Modern Environmental Ethics:An Ecocritical Reading of Piranesi by Susanna Clarke - Myśliwiec, Katarzyna (Jan Kochanowski University Press, 2024)
The article recognizes the need to complement the existing criticism on Piranesi by Susanna Clarke with acknowledgement of the deep concern for current environmental problems evinced by that text. Employing ecocritical literary theory, it calls into question the dichotomy between fantasy literature and contemporary concerns of the primary reality. By exploring two alternative models of human relationship with the House, the secondary world entered by the characters of that portal fantasy novel, the article seeks to prove that they may serve as actual models of environmental practices and ethical stances on the relationship between man and nature. It argues that Piranesi proposes a certain form of animism as a solution to modern man’s alienation from his natural environment. Moreover, it suggests that a return to the childlike state of wonder and recognition of one’s multidimensional connection with one’s place of living is a necessary remedy for the science and greed-driven devastations of nature. The novel’s environmental ethics are interpreted in the context of Barfield’s concept of Original Participation. Using Foucault’s concept of heterotopia, the article establishes Clarke’s House as an example of heterotopia of compensation stressing the contemporary cultural silence of the Earth.